Genética dos teores de cálcio e de ferro em grãos de feijão comum - Jost, Evandro (2008)
The common bean has significant levels of calcium and iron in grains, providing that this legume is used in human food controlling minerals deficiency. Furthermore, genetic variability for these minerals were observed, allowing the development of nutraceutics germplasm. As knowledge about the genetics of calcium levels and iron content are essential for increasing their concentration in grain, and this information is not available in the literature, were objectives of this work: (1) to investigate the occurrence of maternal effect to the levels of calcium and iron in common bean grains (2) to estimate heritability and gain from selection in early generations to the levels of calcium and iron in common bean grains. Therefore, controlled crossings were made between cultivars Pérola x TPS Bonito and TPS Bonito x BRS Expedito, for the study of genetics of calcium, and between cultivars Minuano x Diamante Negro and Diamante Negro x Iapar 44 for the study of genetics of iron. Maternal effect was observed in the expression levels of calcium and iron content common bean grains. For calcium, estimates of heritability, in the broad sense, of 66.75% and 74.65%, and in the narrow sense of 47.00% and 63.61% were obtained for the crossings between Pérola x TPS Bonito and TPS Bonito x BRS Expedito respectively. F2 plant with 33.64% more calcium (1.47 g kg-1 DM) than the genitor with greater value of this mineral, was obtained. For the content of iron, the estimative of heritability, in the broad sense in 76.36% and, in the narrow sense in 50.60% it was observed, from crossing between Minuano x Diamante Negro. It was possible to increase by 94% the iron content, for the genitor of higher mineral content of this because a plant F2 with 161.20 mg kg-1 DM was obtained. The selection of plants in the F2 generation obtained from these crossings can be made effective in the development of common bean germplasm with higher levels of calcium and iron content in grains because of the moderate to high estimates of heritability and gain from selection.